Pelaksanaan Pendidikan Agama Islam Keluarga Muallaf di Desa Jangkang Kecamatan Pasak Talawang Kabupaten Kapuas - Muliatul Muliatul; Muslimah Muslimah; Saudah Saudah; Sri Hidayati (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Implementation of Islamic Education For Muallaf Family In Jangkang Village, Pasak Talawang District, Kapuas RegencyThis study to describe theimplementation of Islamic religious education for families of converts to Islam in the village of Jangkang, Pasak Talawang district Kapuas Regency and to determine the inhibiting and supporting factors for the implementation of Islamic religious education for converts to Islam in the village of Jangkang, Pasak Talawang District, Kapuas Regency. This research uses descriptive qualitative research. Data collection uses oobservation, interviews and documentation, while data validation uses source triangulation. While the data analysis used is data reduction, data display, verification. The results of this study describe: 1) The implementasion of Islamic education, for converts to Islam in the villageof Jangkang, Pasak Talawang District, Kapuas Regency, is realized trough the purpose of implementing Islami religious education, trough Islamic education methods, trough Islamic religous education materials. 2) The inhibiting and supporting factor for the implimentation fo Islamic religious education for converts to Islam in the village of Jangkang, Pasak Talawang District, Kapuas Regency include supporting factor for the faith attached to convert’s parent, strong motivation/ willinges andability tomanagetime to teach their children the existence of a family that guides and teaches about Islam, educational institut lons such as TPA While theinhibiting factors are weak faith, lack of motivation/ willingness to learn Islam and Islamic families do not guide.Abstrak: Pelaksanaan Pendidikan Agama Islam Keluarga Muallaf Di Desa Jangkang Kecamatan Pasak Talawang Kabupaten KapuasPenelitian ini bertujuan untuk mendeskripsikan pelaksanaan pendidikan agama Islam keluarga muallaf di desa Jangkang Kecamatan Pasak Talawang Kabupaten Kapuas dan untuk mengetahui faktor penghambat dan pendukung pelaksanaan pendidikan agama Islam keluarga muallaf di desa Jangkang Kecamatan Pasak Talawang Kabupaten Kapuas. Penelitian ini menggunakan penelitian kualitatif deskriptif. Pengumpulan data menggunakan observasi, wawancara dan dokumentasi, sementara pada pengabsahan data menggunakan trianggulasi sumber. Sedangkan analisis data yang digunakan adalah data reduction, data display, verification. Hasil penelitian ini mendeskripsikan tentang: 1) Pelaksanaan pendidikan agama Islam keluarga muallaf di desa Jangkang Kecamatan Pasak Talawang Kabupaten Kapuas di wujudkan melalui tujuan pelaksanaan pendidikan agama Islam, melalui metode pendidikan agama Islam, melalui materi pendidikan agama Islam. 2) Faktor pendukung dan penghambat pelaksanaan pendidikan agama Islam keluarga muallaf di desa Jangkang Kecamatan Pasak Talawang Kabupaten Kapuas meliputi faktor pendukung terhadap keimanan yang melekat pada diri orang tua muallaf, motivasi/ kemauan yang kuat dan kemampuan memanagemen waktu untuk mengajarkan anaknya adanya keluarga yang membimbing dan mengajarkan tentang agama Islam, lembaga pendidikan seperti TPA. Sedangkan faktor penghambat yaitu keimanan yang lemah, tidak adanya motivasi/ kemauan untuk belajar agama Islam serta keluarga Islam tidak membimbing.